Tumor markers for the medullary thyroid carcinoma - Grauer, Andreas; Blind, Eberhard (Medullary thyroid carcinoma, 1992)
The medullary thyroid carcinoma (MTC) is a malignancy of the C-cell, which originates from the neural crest. In avian or teleost species, the C-cells form a separate organ, the ultimobranchial body. In mammals, however, the C-cells migrate into the thyroid during embryonic life. Within the thyroid the C-cells are located adjacent to but outside the thyroid follicle (parafollicular cells). Their neuroendocrine origin implies several features which differentiate them from follicular epithelium. These features include an uptake mechanism for biogenic amines and the production of several small polypeptide hormones, including products of the calcitonin gene like calcitonin (CT), calcitonin gene-related peptide (CGRP) and others (Bussolati and Pearse 1967; Pearse 1968). Despite their proximity there is little information as to whether hormonal or cellular interactions between the follicular epithelium and the C-cell exist.